Updated ranges of the Vulnerable cheetah and Endangered African wild dog in Angola. Issue 6 (12th November 2020) - Monterroso, Pedro; Rocha, Filipe; van Wyk, Stefan; António, Telmo; Chicomo, Milcíades; Kosmas, Selma; Lages, Fernanda; Fabiano, Ezequiel; Godinho, Raquel
Abstract: The civil unrest that ravaged Angola for nearly 30 years took a heavy toll on the country's wildlife, and led to a lengthy absence of reliable information for many threatened species, including the cheetah Acinonyx jubatus and African wild dog Lycaon pictus . Using camera trapping we assessed the status of these two species in two areas of southern Angola, and complemented our findings by reviewing recent survey reports and observations to provide an update on the species' status. We found unequivocal evidence that African wild dogs are resident and reproducing in Bicuar National Park, where cheetahs appear to be absent. Conversely, cheetahs may be resident in western Cuando Cubango province, where African wild dogs may only be transient. Based on these and other recent records in Angola, we recommend a revision of these species' distribution ranges and note the need for monitoring of these remnant populations and for appropriate attention to any threats.